Economic Empowerment of Banjarwangi Village Community through Various Flavors of Sweet Potato Chips Products - Yumsinah, Siti; Gumilang, Ahmad Agung; Hayati, Sri; Zahrotuhayaty, Ghafera Kamelia (LPPM STAI Darul Falah, 2024)
This article discusses about Community Service Program (KKN) in developing Micro, Small, and Medium Enterprises (MSMEs) in Banjarwangi Village, Pandeglang Regency, Banten Province. Sweet potato is one of the main commodities in this village. Unfortunately, it is still underutilized. Community service program students provide training to the community in processing sweet potatoes into chips with various flavors. The lack of knowledge to develop and innovate in producing food in the form of snacks has become a problem in developing the community in Banjarwangi Village. The purpose of this study is to develop the community's economy through sweet potato chips with various flavors. The results of this activity create profitable business opportunities and increase the income of the local community. This includes methods of implementing activities, results, and marketing strategies for sweet potato chip products. The results of this community service had a positive impact and showed the potential for developing local products that have increasing selling value. As a result, the community in Banjarwangi Village can develop and innovate MSMEs products to help increase household income. The training method provides new learnings in Banjarwangi Village so that the community can face the problems that challenge farmers in utilizing sweet potato.